2016
DOI: 10.1007/s41125-016-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

“Accepting the Rules of the Game”: Institutional Rhetorics in Legitimizing Surveillance

Abstract: In this contribution, we analyze a comprehensive set of rhetorical strategies used by security professionals to legitimize the implementation of advanced surveillance systems. Drawing on a set of semi-structured in-depth interviews with experts from safety and security departments of an air traffic control provider in Italy, we show that both the expressed demands for surveillance as well as the rhetorical strategies used to legitimize its enforcement are embedded in dedicated institutional frameworks. We argu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Surveillance technologies, such as OSINT, have been researched in the context of public security to monitor terrorists and criminal groups. Their capability to monitor the public on a large scale, as well as existing cases thereof have also been researched [10,39]. Surveillance can be defined as the systematic monitoring of individuals or groups for a given purpose [32,52].…”
Section: Acceptance Of Surveillance Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveillance technologies, such as OSINT, have been researched in the context of public security to monitor terrorists and criminal groups. Their capability to monitor the public on a large scale, as well as existing cases thereof have also been researched [10,39]. Surveillance can be defined as the systematic monitoring of individuals or groups for a given purpose [32,52].…”
Section: Acceptance Of Surveillance Technologiesmentioning
confidence: 99%
“…As OSINT in cybersecurity draws insights from the fields of crisis informatics [4,44] as well as surveillance studies [39], the research from similar cases can be used to derive implications for the design of OSINT systems and their evaluation regarding the factors which are associated with the acceptance of such systems. The discourse on privacy and relevant context factors [36,37] has shown that the following aspects need further consideration: the kind of data which is collected (1), the actors or organization gathering the data (2) and the transmission principles and platforms which allow for the data gathering (3).…”
Section: Implications For Design and Organizationmentioning
confidence: 99%
“…Surveillance technologies, such as OSINT, have been researched in the context of public security to monitor terrorists and criminal groups. Their capability to monitor the public on a large scale, as well as existing cases thereof have also been researched [10,39]. Surveillance can be defined as the systematic monitoring of individuals or groups for a given purpose [32,52].…”
Section: Acceptance Of Surveillance Technologiesmentioning
confidence: 99%
“…The increased access to information technology for private users as well as for security organizations has led to the increased use of "surveillance-oriented security technologies" (SOSTs). SOSTs are technologies that are designed to monitor terrorists and criminal groups but are also capable of and have been used to monitor the public on a large scale (Degli Esposti & Santiago Gómez 2015, p. 437;Pauli et al 2016). The acquisition of SOSTs has been legitimized as means to prevent criminal and terrorist attacks; however, it has also led to critical discussions of surveillance measures (Ball et al 2012;Bauman et al 2014;Bigo 2006;Lyon 2006).…”
Section: Surveillance Studies Perspective On Security Practicesmentioning
confidence: 99%